Graphene oxide Janus nanosheet of metal-polyphenol network as well as preparation method and application of graphene oxide Janus nanosheet
By modifying the metal-polyphenol network on graphene oxide nanosheets, TA-Ti/GO/NH2-PS JNSs are formed as emulsifiers to encapsulate and release EOs, which solves the problems of EOs volatility and poor water solubility, enhances its antibacterial effect, and imparts various functions to the nanosheets.
Patent Information
- Application Number
- CN202411735268.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-04
AI Technical Summary
Natural plant essential oils (EOs) are volatile at room temperature, have poor water solubility, are easily oxidized and have a pungent odor, which limits their antibacterial application scenarios, and the drug resistance, biotoxicity and environmental pollution caused by chemical fungicides are serious.
The metal-polyphenol network was modified on graphene oxide (GO) nanosheets by template protection to form graphene oxide Janus nanosheets (TA-Ti/GO/NH2-PS JNSs) with metal-polyphenol networks, and used them as emulsifiers to encapsulate and release EOs to form Pickering emulsions to enhance the antibacterial effect.
The problem of EOs being volatile and poor water solubility at room temperature is solved, its antibacterial effect is enhanced, and the nanosheet interface adhesion, resistance to ultraviolet and antioxidant ability is imparted through the polyphenol-metal network structure, forming a stable and efficient EOs delivery system.
Smart Images

Figure CN119551669A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of emulsion preparation, and in particular to a metal-polyphenol network graphene oxide Janus nanosheet and a preparation method and application thereof. Background Art
[0002] Plant-based natural essential oils (EOs) are important secondary products extracted from different parts of plants, mainly containing terpenes and phenolic compounds with a wide range of activities. Based on the broad antioxidant, antibacterial and nutritional effects of EOs, they are widely used in pharmacology, medicine, food and other fields, but there are few studies on the inhibitory effects of EOs on plant pathogens. At present, the reported antibacterial mechanism of EOs is to destroy the cell structure of fungi through active components and produce reactive oxygen to inhibit the growth and reproduction of pathogens. Therefore, EOs have potential application value in resisting plant pathogens. It is well known that the use of chemical fungicides such as triazoles, methacrylates, amides, etc. is a key means to prevent and solve plant diseases caused by plant pathogens. However, the problems of drug resistance, biological toxicity, environmental pollution, food safety, etc. caused by chemical fungicides are becoming more and more serious. Studies have confirmed that EOs such as thymol, carvacrol, limonene, eugenol, etc. have excellent comprehensive antibacterial properties, and fungi will not develop drug resistance. However, EOs are highly volatile at room temperature, difficult to dissolve in water, easily oxidized in the air, and have a pungent odor. These shortcomings reduce the antibacterial ability of EOs and also limit their application scenarios. Therefore, building a green and efficient EOs encapsulation and delivery system is of great significance to expand its practical application.
[0003] Pickering emulsion is a W / O or O / W emulsion formed by solid particles as emulsifiers. Compared with small molecule surfactants and isotropic solid particles, two-dimensional Janus nanosheets (2D JNSs) exhibit excellent emulsification properties due to their high specific surface area, high anisotropy of structure and properties, and restricted interface rotation. Studies have shown that JNSs have higher desorption energy at the oil-water interface, which can significantly enhance the stability of oil emulsions and prevent the leakage of encapsulated active substances. At present, the reported methods for preparing JNSs mainly include interface protection method, phase separation method, self-assembly method, and template protection method, but these methods have problems such as complex operation, use of multiple initiators and organic solvents, monomer type restrictions, and low yield. Therefore, a simple, general, green and mild preparation strategy for the synthesis of functionalized JNSs is of great significance.
[0004] Graphene oxide (GO), as a rigid hydrophilic 2D material, is covered with hydroxyl, carboxyl, and epoxy active functional groups and is an ideal template for the synthesis of JNSs. Polyphenol monomers (tannic acid, dopamine, gallic acid, and epicatechin) with diverse structures, simple polymerization, and easy functionalization are used to react with metal ions (such as Cu 2+ , Fe 3+ 、Zn 2+ 、Ti 4+ The metal-polyphenol network GO JNSs can be prepared by complexing with metal-polyphenols (such as EOs) to form functionalized metal-polyphenol networks (MPNs) on the GO surface. This material combines the advantages of JNSs and MPNs, giving Pickering emulsions specific functions: such as enhanced emulsion stability, interfacial adhesion, UV resistance, antioxidant, synergistic antibacterial, etc., providing an ideal carrier for the encapsulation, release, and antibacterial activity enhancement of EOs. Summary of the invention
[0005] The purpose of the present invention is to provide a metal-polyphenol network graphene oxide Janus nanosheet and its preparation method and application. Based on a deep understanding of JNSs synthesis, EOs Pickering emulsion preparation method and EOs antibacterial mechanism, it is proposed to use a template protection method to prepare a metal-polyphenol network GO JNSs and use it to form EOs Pickering emulsion for plant disease prevention and control. Using GO JNSs as a solid emulsifier to encapsulate EOs can solve the problem of EOs being volatile and poorly soluble in water at room temperature, and can also synergize with the adjuvants in the system to enhance antibacterial performance.
[0006] The scheme of the present invention is:
[0007] A metal-polyphenol network graphene oxide Janus nanosheet comprises a hydrophobic unit provided by a solid template and a hydrophilic unit provided by a metal-polyphenol network coating; the metal-polyphenol network graphene oxide Janus nanosheet is obtained by a solid template protection method followed by metal-polyphenol modification;
[0008] As a preferred technical solution, the solid template is polystyrene (PS), amino polystyrene (NH2-PS), polymethyl methacrylate (PMMA), solid paraffin as a template, and further preferably NH2-PS as a template;
[0009] When the metal-polyphenol network is modified on the outside of GO, the polyphenol monomer can be tannic acid (TA), dopamine, gallic acid and epicatechin, and the further preferred polyphenol monomer is tannic acid (TA);
[0010] Metal is Cu 2+ , Fe 3+ 、Zn 2+ 、Ti4+ One of the above, further preferably Ti 4+ (Titanium diammonium bis(2-hydroxypropionate) dihydroxide, Ti-BALDH).
[0011] As a preferred technical solution, the sheet diameter of the graphene oxide Janus nanosheet of the metal-polyphenol network is micrometer-level, and its thickness is 4.5nm as measured by AFM; the graphene oxide Janus nanosheet of the metal-polyphenol network is TA-Ti / GO / NH2-PS nanosheet, including a hydrophilic unit provided by TA-Ti and a hydrophobic unit provided by NH2-PS;
[0012] The TA-Ti / GO / NH2-PS nanosheet is obtained by using graphene oxide as a template and then being modified by TA-Ti.
[0013] The present invention also discloses a method for preparing metal-polyphenol network graphene oxide Janus nanosheets, comprising the following steps: in a mixed solution, graphene oxide and NH2-PS are electrostatically adsorbed, the metal-polyphenol network coating is used to modify the outer side, and the template is washed away to obtain the metal-polyphenol network graphene oxide Janus nanosheets, wherein the mixed solution is a mixture of ethanol and water.
[0014] As a preferred technical solution, the following steps are included:
[0015] S1. Graphene oxide is combined with a solid template through non-covalent interaction. A solid template with a diameter of 1 μm is dispersed in a mixed solution, graphene oxide is added, and stirred at a stirring speed of 500 to 800 rpm to adsorb the graphene oxide on the solid template; the volume ratio of ethanol to water in the mixed solution is 1:1 to 3;
[0016] S2, modification of the metal-polyphenol network coating, adding polyphenol and metal to the product obtained in step S1, dispersing in a mixed solvent of Tirs-HCl buffer and water, stirring at a stirring speed of 500 to 800 rpm for 10 to 60 min, to obtain microspheres with the metal-polyphenol network coating modified on the outer side of the nanosheet;
[0017] S3, etching the microspheres obtained in step S2 with an organic solvent to obtain metal-polyphenol network graphene oxide Janus nanosheets; the organic solvent is one of n-hexane, ethyl acetate, dichloromethane and tetrahydrofuran.
[0018] As a preferred technical solution, the following steps are also included:
[0019] The step S1 also includes the purification of NH2-PS@GO. After the reaction in step S1 is completed, the reaction solution in step S1 is washed and centrifuged with a mixed solution for multiple times to remove unreacted graphene oxide and NH2-PS, and the obtained solid is placed in a vacuum drying oven at 40 to 60° C. and dried for 6 to 8 hours;
[0020] The S3 also includes the purification of GO JNSs. After the reaction in step S3 is completed, the reaction solution in step 3 is washed and centrifuged with a mixed solution for multiple times to remove the solid template. The precipitate finally centrifuged is washed and filtered with a mixed solution. The obtained solid is placed in a vacuum drying oven at 40 to 60° C. and dried for 6 to 12 hours to obtain the metal-polyphenol network graphene oxide Janus nanosheets.
[0021] As a preferred technical solution, the mixed liquid is ethanol and water, and the volume ratio of ethanol to water is 1:2; the stirring speed in the step S1 is 600-700 rpm.
[0022] The modification of the metal-polyphenol network coating is S1 adding TA and Ti-BALDH to the prepared template, the molar ratio of TA to Ti-BALDH is 1:1-3, more preferably 1:1, and the stirring speed of S2 is 600-700rpm; the reaction is carried out under weak alkaline conditions, and the reaction time is 15-30min.
[0023] The S3 is washed with anhydrous ethanol and centrifuged, and the cycle is repeated 3-4 times, and the obtained solid is placed in a vacuum drying oven at 50-60° C. for 6-8 hours to finally obtain TA-Ti / GO / NH2-PS JNSs.
[0024] The invention also discloses an emulsifier, which is a graphene oxide Janus nanosheet of a metal-polyphenol network.
[0025] The invention also discloses a plant essential oil Pickering emulsion, which is formed by using metal-polyphenol network graphene oxide Janus nanosheets as an emulsifier.
[0026] As a preferred technical solution, the Pickering emulsion is an oil-in-water emulsion; in the Pickering emulsion, the volume ratio of the oil phase to the water phase is 1-10:90-99; in the Pickering emulsion, the concentration of the metal-polyphenol network graphene oxide Janus nanosheets is 0.5-4 mg / mL;
[0027] The Pickering emulsion is obtained by dispersing the metal-polyphenol network graphene oxide Janus nanosheets of claim 1 into a water phase, adding an auxiliary agent, and then mixing and emulsifying the water phase with an oil phase;
[0028] The oil phase is one or more of natural plant essential oils such as citronella oil, thymol, carvacrol, turpentine and eugenol; the pH of the water phase is 1 to 12;
[0029] The auxiliary agent is one or more of chitosan, quaternized chitosan, chitin and gum arabic;
[0030] The Pickering emulsion has a pH stability value of 3-11.
[0031] As a preferred technical solution, the EOs Pickering emulsion formed by using TA-Ti / GO / NH2-PS JNSs is of O / W type, and the JNSs concentration is 1.0-2.0 mg / mL.
[0032] As a preferred technical solution, the oil phase is turpentine and eugenol (EU).
[0033] As a preferred technical solution, the auxiliary agent is quaternized chitosan (QCS), and the mass fraction of QCS is 0.25wt%-1wt%, and further preferably 0.75wt%-1wt%.
[0034] As a preferred technical solution, citric acid and NaOH are selected as pH regulators.
[0035] As a preferred technical solution, the Pickering emulsion pH is 7 as the emulsion preparation condition.
[0036] The invention also discloses an application of a plant essential oil Pickering emulsion for preventing and treating fungal diseases caused by plant foliar fungi, wherein the fungal disease is resistance to tomato gray mold.
[0037] As a preferred technical solution, JNSs-EU-PE was diluted 1-200 times, added to PDA medium, and inoculated with Botrytis cinerea Pers.Fr. to study the antibacterial effect of JNSs EU PE concentration gradient on B. cinerea. The minimum effective antibacterial concentration was used to solve plant diseases caused by plant foliar fungi in the agricultural field.
[0038] A metal-polyphenol network graphene oxide Janus nanosheet and its preparation method and application are adopted, which includes a hydrophobic unit provided by a solid template and a hydrophilic unit provided by a metal-polyphenol network coating; the metal-polyphenol network graphene oxide Janus nanosheet is obtained by a solid template protection method followed by metal-polyphenol modification.
[0039] Advantages of the present invention:
[0040] The present invention uses a template protection method to modify the metal-polyphenol network on the outside of the GO nanosheet. After etching the template, the inside is hydrophobic NH2-PS and the outside is hydrophilic MPNs. Polyphenols give the nanosheets excellent interfacial adhesion, so that the GO JNSs are firmly anchored on the interface. The introduction of metal ions and polyphenol complexation can reduce the aggregation of polyphenols to obtain a uniform MPNs hydrophilic layer; at the same time, the antibacterial properties of MPNs can be used to synergize EOs to enhance the antibacterial effect.
[0041] Compared with the disadvantages of small molecule surfactants, such as large dosage, poor stability and lack of functionality, the metal-polyphenol network GO JNSs prepared by the present invention have excellent amphiphilic properties, low emulsifier concentration required to form a stable Pickering emulsion, uniform droplets with a particle size of less than 10 μm, and faster migration rate on the interface. The modified polyphenol-metal network structure can give GOJNSs beneficial effects such as interface adhesion, UV resistance, antioxidant, and synergistic antibacterial.
[0042] Commercially available fungicides are applied in large amounts and have a single antibacterial property, which can easily cause plant pathogens to develop drug resistance, and residues in the environment will pose a threat to human safety. However, EOs, as important secondary metabolites extracted from plants, have a wide range of sources, are green and environmentally friendly, and have no phytotoxic effects. Using EOs as the oil phase to form a Pickering emulsion fully utilizes the broad-spectrum antibacterial properties of EOs, and solves the problems of EOs being volatile, poorly water-soluble, easily oxidized, and having a pungent odor at room temperature. The EOs Pickering emulsion formed by the present invention has good stability at pH = 3-11, which can greatly expand the application scenarios of the emulsion, which is also an effect that small molecule surfactants cannot achieve. Moreover, the metal-polyphenol network GO JNSs adsorbed on the surface of EOs are firmly "anchored" on the interface between EOs and water through non-covalent interactions between polyphenols, between polyphenols and EOs, and between polyphenols and other added components (such as QCS), thereby achieving stable encapsulation and release of EOs. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is a flow chart for the preparation of TA-Ti / GO / NH2-PS JNSs and JNSs-EU-PE in the present invention;
[0044] Figure 2 The electronic scanning images of TA-Ti / GO / NH2-PS JNSs of Example 5 of the present invention, wherein a is a SEM image, b is a TEM image, and c is an AFM image;
[0045] Figure 3 This is the water contact angle diagram on both sides of TA-Ti / GO / NH2-PS JNSs of Example 5 of the present invention;
[0046] Figure 4The photographs of the bouncing behavior of Test 1 of the present invention; wherein a is the bouncing behavior of water, TW-80-EU-E, JNSs-EU-PE and EU-EW on the hydrophobic paraffin layer, the normalized height b and normalized diameter c of the droplet change with time, and d is the bouncing behavior of water, TW-80-EU-E, JNSs-EU-PE and EU-EW on tomato leaves at 0°, 30° and 60°;
[0047] Figure 5 This is a comparison diagram of the components in Test 2 of the present invention on tomato leaves; a is the adhesion process of water, TW-80-EU-E, JNSs-EU-PE and EU-EW on tomato leaves; b is the relationship between the droplet position and weight; c is the different droplet breakup distances and residual masses; d is the contact angle and deposition amount of water, TW-80-EU-E, JNSs-EU-PE and EU-EW on tomato leaves; e is the CLSM image of tomato leaves before and after washing with EU marked with Nile red, scale: 10 μm;
[0048] Figure 6 It is a comparison chart of the moisturizing performance and absorption efficiency on tomato leaves in Test Example 3 of the present invention, wherein a is the SEM of TW-80-EU-E, JNSs-EU-PE and EU-EW deposited on tomato leaves for 0h and 12h, scale: 50μm; b is a photo of the residual droplets of JNSs-EU-PE and EU-EW on tomato leaves; c is the change of leaf mass loss over time after treatment with JNSs-EU-PE and EU-EW; d is the CLSM image of tomato roots, stems and leaves after treatment with Nile Red labeled EU, scale: 100μm;
[0049] Figure 7 The test effect diagram of test 4 of the present invention; a is a photo of the QCS and JNSs anti-Botrytis cinerea plate test; b is the in vitro antibacterial activity of QCS and JNSs; c is a photo of the TW-80-EU-E, JNSs-EU-PE and EU-EW anti-Botrytis cinerea plate test; d is the in vitro antibacterial activity of TW-80-EU-E, JNSs-EU-PE and EU-EW; e is the EC of TW-80-EU-E, JNSs-EU-PE and EU-EW 50 ; f is the SEM of Botrytis cinerea hyphae after normal growth, scale bar: 50μm; g is the SEM of Botrytis cinerea hyphae after JNSs-EU-PE treatment, scale bar: 50μm; h is the CLSM image of Botrytis cinerea before and after EU treatment with Nile red, scale bar 10μm;
[0050] Figure 8The figures are comparative diagrams of the antibacterial effects of the five emulsions tested in the present invention; a is a photo of the growth of gray mold cakes on tomato fruits treated with TW-80-EU-E, JNSs-EU-PE, EU-EW and BSC-PMT-SC within 4 days; b is the lesion area of tomatoes after treatment with TW-80-EU-E, JNSs-EU-PE, EU-EW and BSC-PMT-SC; c is the inhibition rate of gray mold growth after treatment with TW-80-EU-E, JNSs-EU-PE, EU-EW and BSC-PMT-SC.
[0051] Fig. 9 The photos of the growth of gray mold on tomato leaves treated with TW-80-EU-E, JNSs-EU-PE, EU-EW and BSC-PMT-SC in Test 6 of the present invention within 4 days;
[0052] Fig.10 This is a comparison chart of the cytotoxicity test in Test 7 of the present invention; including the relative cell survival rate after 24 hours of treating L0-2 cells with JNSs-EU-PE and EU-EW. DETAILED DESCRIPTION
[0053] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments.
[0054] The following examples are only used to further illustrate the present invention in detail, but do not constitute any limitation to the present invention; the materials used in the following examples, unless otherwise specified, were purchased from conventional chemical reagent companies and raw material suppliers.
[0055] Embodiment 1:
[0056] like Figure 1 As shown, the process flow was used to prepare TA-Ti / GO / NH2-PS JNSs.
[0057] In the first step, 20 mL of GO nanosheet aqueous dispersion was added to a beaker and diluted with deionized water, and NH2-PS microspheres were weighed and dispersed in anhydrous ethanol.
[0058] In the second step, the ethanol solution containing NH2-PS microspheres was added to the GO aqueous solution, and the stirring speed was selected to be 700 rpm and the stirring time was 12 h.
[0059] In the third step, after the reaction, centrifuge at 10,000 rpm for 3 min and wash with anhydrous ethanol and water. Repeat the operation for 3-5 times and place the obtained solid in a vacuum drying oven at 60°C for 6-8 hours.
[0060] Embodiment 2:
[0061] The preparation method is the same as that in Example 1, except that NH2-PS microspheres are replaced by PS microspheres.
[0062] Embodiment 3:
[0063] The preparation method is the same as that in Example 1, except that the NH2-PS microspheres are replaced with PMMA microspheres.
[0064] Embodiment 4:
[0065] In the first step, a GO aqueous dispersion was prepared, solid paraffin (melting point 54-56°C) was added, and the mixture was heated to a temperature above the melting point of the solid paraffin. After emulsification, the mixture was naturally cooled to room temperature.
[0066] Embodiment 5:
[0067] In the first step, the solid product in Example 1 is weighed and added into deionized water for ultrasonic dispersion.
[0068] Step 2: Add TA to Ti-BALDH in a round-bottom flask at a mass ratio of 3:1. Add Tirs-HCl buffer to control the solution pH to 8.5. Stir at 700 rpm and react for 30 min.
[0069] In the third step, after the reaction, centrifuge at 8000 rpm for 3 min and wash with anhydrous ethanol and water, repeating the operation 3-5 times.
[0070] Step 4: Add a mixture of THF and water (v / v, 10:1) to the product of the previous step and subject it to ultrasonic etching. Centrifuge at 10,000 rpm for 3 min and wash with anhydrous ethanol for 3-5 cycles. Dry in a vacuum oven at 60°C for 6 h to obtain TA-Ti / GO / NH2-PS JNSs.
[0071] Comparative Example 5-1:
[0072] The preparation method is the same as that of Example 5, except that only TA is added, and Ti-BALDH is not added.
[0073] Comparative Example 5-2:
[0074] The preparation method is the same as that of Example 5, except that the polyphenol monomer is replaced by dopamine hydrochloride.
[0075] Comparative Example 5-3:
[0076] The preparation method is the same as that of Example 5, except that Ti-BALDH is replaced by TiCl3.
[0077] Comparing Example 5, Comparative Example 5-1 and Comparative Example 5-2, the coordination between the metal and the polyphenol in Example 5 makes the coating more uniform and smooth, and the use of TA as the polyphenol monomer has a more ideal effect. Figure 2 (a) It can be seen that the morphologies of the two sides of TA-Ti / GO / NH2-PS JNSs are different. The metal-polyphenol network side is relatively rough, while the NH2-PS side is relatively smooth. Figure 2 (b) is the TEM of TA-Ti / GO / NH2-PS JNSs. AFM test shows that the thickness of the prepared nanosheets is 4.5nm, which is significantly different from the original GO thickness of 1.5nm. The TA-Ti / GO / NH2-PS JNSs membrane was prepared by the self-assembly behavior of TA-Ti / GO / NH2-PS JNSs at the oil-water interface. Figure 3 The static water contact angles on both sides of the membrane were 76.70° and 117.37°, respectively, indicating that the TA-Ti / GO / NH2-PS JNSs prepared in Example 5 have amphiphilic properties.
[0078] Embodiment 6:
[0079] Preparation of Eugenol (EU) Pickering emulsion.
[0080] In the first step, the TA-Ti / GO / NH2-PS JNSs obtained in Example 5 were dispersed in deionized water at a concentration of 1 mg / mL.
[0081] In the second step, 7.5% EU by volume was transferred to a screw-cap bottle, and 0.75 wt% QCS was added, and ultrasonic emulsification was performed to obtain O / W EU Pickering emulsion (JNSs-EU-PE).
[0082] Comparative Example 6-1:
[0083] The same mass fraction of TW-80 aqueous solution and EU (volume fraction 7.5%) were mixed and ultrasonically emulsified to obtain EU emulsion (TW-80-EU-E).
[0084] Comparative Example 6-2:
[0085] Deionized water was used to dilute a commercially available 20% EU aqueous emulsion, wherein the effective concentration of EU was the same as that in Example 5, and the prepared sample was called EU EW.
[0086] Embodiment 7:
[0087] According to the emulsion preparation procedure in Example 6, the pH of the aqueous phase was changed (pH=3-11).
[0088] Embodiment 8:
[0089] According to the emulsion preparation process in Example 6, the JNSs concentration was changed to 0.3, 0.5, 0.7, and 1.0 (mg / mL).
[0090] Embodiment 9:
[0091] The emulsion preparation process in Example 6 was followed, with the EU volume fraction being changed (2.5%, 5%, 7.5%, 10%).
[0092] Embodiment 10:
[0093] According to the emulsion preparation process in Example 6, the EU volume fraction was determined to be 7.5%, and the QCS mass fraction was changed to 0.25, 0.5, 0.75, and 1.0 (wt%).
[0094] Test Example 1:
[0095] The bouncing behavior of EU emulsions on hydrophobic paraffin layers and tomato leaves was evaluated.
[0096] Test method: Take pictures with a high-speed camera.
[0097] Test process: After the samples in Example 6 and Comparative Examples 6-1 to 6-2 were diluted 100 times, the bouncing behavior of the above dilutions on a clean hydrophobic paraffin layer and tomato leaves was studied by a high-speed camera.
[0098] Depend on Figure 4 (ac) It can be seen that deionized water rebounds completely on the hydrophobic paraffin layer, and the maximum spreading diameter is the smallest. The rebound height of JNSs-EU-PE on the hydrophobic paraffin layer is lower than that of the emulsion formed by the small molecule surfactant TW-80, and the maximum spreading diameter is larger than that of the commercially available EU water emulsion, which proves that JNSs-EU-PE has good wetting and spreading ability. Figure 4 (d) It can be seen that deionized water, TW-80-EU-E and EU-EW will bounce and splash to varying degrees when in contact with tilted tomato leaves, resulting in a large loss of effective ingredients. JNSs-EU-PE has a wetting and spreading ability that is significantly better than TW-80-EU-E because of its adhesion to polyphenols, low interfacial free energy of the emulsion system, and hydrogen bonding interaction with the leaf surface. On leaves at an inclined angle, the rebound and rolling effects of JNSs-EU-PE are much weaker than those of TW-80-EU-E and EU-EW. This is attributed to the fact that JNSs slides relatively on the leaves under the influence of gravity, and can continuously modify the leaves over a larger area.
[0099] Test Example 2:
[0100] The adhesion, deposition amount and rainwater resistance of different emulsions on tomato leaves were evaluated.
[0101] Test process: During the application of pesticide emulsions, factors such as off-target and rebound splashing of droplets on the leaf surface will affect the actual use effect of the pesticide. The adhesion test of droplets on leaves can evaluate the ability of droplets to quickly wet and spread after contact with the leaf surface. After the droplets come into contact with the leaf surface, they will be affected by gravity, causing a large number of droplets to fall off the leaf surface. The Wilhelmy method is used to determine the final deposition amount of droplets under the influence of gravity. After the pesticide is deposited on the leaf surface, it will be washed away by rain and the active ingredients will enter the soil with the rain, which will be inefficient and cause environmental pollution. The pesticide is fluorescently labeled, and the rain scouring experiment is carried out on the leaves after the pesticide is applied to simulate rain, and the ability of the pesticide to resist rain scouring is evaluated based on the change in fluorescence intensity.
[0102] The tomato leaves were fixed on a glass slide and the adhesion test mode of the surface tension meter was used. The same volume of droplets were hung on the ring for each test to conduct the adhesion experiment.
[0103] Depend on Figure 5 (a) It can be seen that the spreading effect of JNSs-EU-PE on tomato leaves is between TW-80-EU-E and EU-EW. Figure 5 As shown in (bc) (the horizontal axis is the distance between the droplet and the leaf surface, and the vertical axis is the residual mass of the droplet on the ring and the broken distance), it can be obtained that the broken distance of JNSs-EU-PE on the leaf surface is shorter than that of TW-80-EU-E, and the residual amount of JNSs-EU-PE on the leaf surface is 0.008g, which is higher than other emulsions. The shorter the broken distance, the stronger the wetting and spreading ability of the droplet on the leaf surface, which is more conducive to the deposition of the droplet on the leaf surface during application. The larger the residual amount of the droplet on the leaf, the more conducive it is to achieve the purpose of pesticide use. Figure 5 (d) According to the leaf surface deposition experiment and contact angle experiment of the emulsion, it is proved that JNSs-EU-PE can quickly wet the hydrophobic surface (123.71°) (70.74°) after contacting the leaf surface, and the deposition amount can reach 18 mg / cm after the influence of gravity. 2 This is mainly because the polyphenol side of JNSs has excellent adhesion and hydrophilicity, which ensures that the emulsion can quickly wet and spread on the leaf surface. The network structure composed of multiple non-covalent interactions in JNSs-EU-PE weakens the influence of gravity. After fluorescent labeling of the oil phase, the rainwater erosion resistance experiment was carried out. Figure 5 As shown in (e), the residual fluorescence intensity of JNSs-EU-PE is higher than that of other emulsions, which further proves the excellent leaf adhesion effect of JNSs-EU-PE.
[0104] Test Example 3:
[0105] Investigating the moisturizing properties and absorption efficiency of the emulsion on tomato leaves
[0106] Test process: Dilute the samples of Example 6, Comparative Example 6-1 and Comparative Example 6-2 to ensure consistent EU concentration. Spray the diluted samples on tomato leaves, and use SEM to observe the leaf morphology 0h and 12h after spraying. Select leaves of uniform size, spray an equal volume of emulsion on the leaf surface, and weigh the leaf mass at a fixed time. After labeling EU with Nile Red, spray TW-80-EU and JNSs-EU-PE on tomato leaves, and perform fluorescence imaging of tomato leaves, stems and roots 12h later.
[0107] from Figure 6 In (a), after 12 hours of observation, the TW-80-EU and EU-EW droplets on the leaves were relatively dispersed, and the non-covalent interaction in JNSs-EU-PE induced the droplets to present a dense network structure on the leaf surface, forming a surface film to cover the leaves. Leaf Moisture Experiment ( Figure 6 (b), (c)) show that after 95 min, EU-EW completely dried on the leaf surface, but JNSs-EU-PE still remained, with a solution retention rate 12.26% higher than that of EU-EW. Figure 6 (d) shows that after 12 h, the fluorescence signal of JNSs-EU-PE labeling appeared in the stems and roots. This is attributed to the "moisture retention" and "capping effect" that facilitate the internal absorption and transport of the emulsion.
[0108] Test Example 4:
[0109] Inhibition ring experiments were carried out on different emulsions to investigate the inhibitory effects of the emulsions on tomato gray mold and provide a reference for subsequent detached leaf experiments and fruit experiments.
[0110] Test process: The samples of Example 6, Comparative Example 6-1 and Comparative Example 6-2 were diluted and added to PDA medium according to the EU concentration gradient for culture, and the growth diameter of the bacterial cake was measured. The antibacterial rate was calculated according to the following formula, and the half effective concentration (EC 50 ).
[0111]
[0112] Figure 7 (ab) are the antibacterial experiments of QCS and JNSs. The experiments show that both QCS and JNSs have antibacterial properties, with the antibacterial rates of JNSs being 22.54% and QCS being 8.92%. Figure 7 (c) is the plate antibacterial test of Example 6, Comparative Example 6-1 and Comparative Example 6-2. It can be seen from the figure that when the EU concentration reaches 0.8 mg / mL, both JNSs-EU-PE and EU-EW show complete inhibition of the growth of Botrytis cinerea. Figure 7In (d), when the EU concentration was lower than 0.08 mg / mL, the antibacterial effect of JNSs-EU-PE was better than that of other emulsions, which was related to the synergistic antibacterial ability of QCS and JNSs in the emulsion. Figure 7 (e) Get EC 50 , EC of JNSs-EU-PE 50 It is 0.235 mg / mL, which is between TW-80-EU-E (0.507 mg / mL) and EU-EW (0.169 mg / mL), indicating that its antibacterial activity is better than that of the emulsion formed by surfactant. Figure 6 (fg) are SEM images of Botrytis cinerea after normal growth and after being treated with JNSs-EU-PE. It can be seen that the surface morphology of the mycelium changed from rough to relatively smooth after being treated with JNSs-EU-PE. This proves that JNSs-EU-PE achieves the antibacterial effect by destroying the biological barrier of Botrytis cinerea. EU was labeled with Nile red and imaged using confocal laser scanning microscopy (CLSM). Figure 6 (h), JNSs-EU-PE can pass through the biological barrier of Botrytis cinerea hyphae and enter the interior of the hyphae.
[0113] Test Example 5:
[0114] Through Test Example 4, it was determined that the emulsion with an EU concentration of 0.8 mg / mL was used to conduct a tomato fruit anti-gray mold experiment to evaluate the antibacterial effect of each emulsion in a practical scenario.
[0115] Test process: Select several tomatoes of appropriate size, inoculate with Botrytis cinerea with a diameter of 7mm after spraying with liquid medicine, and place the inoculated tomatoes in a constant temperature artificial climate box with a humidity of more than 90% and 25±3℃, and count the incidence every other day. Calculate the preventive effect of different emulsions on the infection of Botrytis cinerea on tomato fruits according to the inhibition rate formula.
[0116]
[0117] Take photos of tomato disease for four consecutive days. Figure 8 As shown in (a), JNSs EU PE showed the mildest infection symptoms after four days. Figure 8 (b) Statistical lesion area. The lesion area of JNSs-EU-PE on the fourth day was 6.52 cm 2 , lower than other treatment groups. Figure 8 (c) The inhibition rate was obtained by converting the lesion area. The inhibitory effect of JNSs-EU-PE on tomato fruits infected with gray mold within four days (31.14%) was comparable to that of the commercially available water emulsion (27.20%) and the current mainstream chemical synthetic pesticide for controlling gray mold (boscalid-pyrimethanil suspension concentrate, BSC-PMT-SC, 28.50%).
[0118] Test Example 6:
[0119] In vitro leaf experiments were performed with each emulsion having an EU concentration of 0.8 mg / mL.
[0120] Test process: Select healthy and uniform-sized tomato leaves, spray them with liquid medicine, and then inoculate them with gray mold with a diameter of 7mm. Place the inoculated leaves in an artificial climate box with a humidity of more than 90% and a constant temperature of 25±3℃, and take photos of the diseased leaves for four consecutive days.
[0121] The disease condition of tomato leaves is shown in Figure (9). After four days of statistics, it was found that the leaves treated with JNSs-EU-PE had the mildest disease symptoms.
[0122] Through tomato fruit and detached leaf experiments, the feasibility of using JNSs-EU-PE formed by GO JNSs as solid emulsifiers and plant essential oils as natural antibacterial agents as surfactant-free, green, and highly effective fungicides was demonstrated.
[0123] Test Example 7:
[0124] Cytotoxicity experiments were performed using JNSs-EU-PE and EU-EW with a gradient of EU concentration.
[0125] Test process: Human hepatocytes (L0-2) in the logarithmic growth phase were inoculated in a 96-well plate. The cells were cultured to adhere to the wall, the culture medium was discarded, and the culture medium containing JNSs-EU-PE or EU-EW was added to each well. The EU concentrations were 0.01, 0.05, 0.1, 0.2, 0.4, 0.6 and 0.8 mg / mL, respectively. The cells were cultured in a 37°C, 5% CO2 incubator for 24 hours. After adding thiazolyl blue (MTT) for culture, dimethyl sulfoxide (DMSO) was used to dissolve the precipitated crystals, and the absorbance value at 490 nm was measured using a multifunctional microplate reader to determine the relative survival rate of L0-2 in different treatment groups.
[0126] After 24 hours of culture, the cell survival rates of JNSs-EU-PE and EU-EW under the EU concentration gradient are shown in Figure (10). When EU is 0.01, 0.05, 0.1, 0.2, 0.4, 0.6 and 0.8 mg / mL, the cell survival rates of JNSs-EU-PE are higher than those of EU-EW. At the EU antibacterial concentration used (0.8 mg / mL), the cell survival rate of JNSs-EU-PE is 55.65%, which is higher than that of EU-PE at 26.47%. Cytotoxicity experiments have shown that JNSs-EU-PE is less harmful to the human body and is safer than using commercial water emulsions.
[0127] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A metal-polyphenol network graphene oxide Janus nanosheet, characterized in that: It includes a hydrophobic unit provided by a solid template and a hydrophilic unit provided by a metal-polyphenol network coating; the metal-polyphenol network graphene oxide Janus nanosheet is obtained by a solid template protection method followed by metal-polyphenol modification; The polyphenol in the metal-polyphenol network layer is one or more of tannic acid, dopamine, gallic acid and epicatechin, and the metal is Cu 2+ , Fe 3+ 、Zn 2+ 、Ti 4+ One or more of; The solid template is one or more of PS, NH2-PS, PMMA, and solid paraffin.
2. The metal-polyphenol network graphene oxide Janus nanosheet according to claim 1, characterized in that: The sheet diameter of the metal-polyphenol network graphene oxide Janus nanosheet is micrometer-level; the metal-polyphenol network graphene oxide Janus nanosheet is TA-Ti / GO / NH2-PS nanosheet, including a hydrophilic unit provided by TA-Ti and a hydrophobic unit provided by NH2-PS; The TA-Ti / GO / NH2-PS nanosheet is obtained by using graphene oxide as a template and then being modified by TA-Ti.
3. A method for preparing a metal-polyphenol network graphene oxide Janus nanosheet as claimed in any one of claims 1 or 2, characterized in that: The method comprises the following steps: in a mixed solution, graphene oxide and NH2-PS are electrostatically adsorbed, a metal-polyphenol network coating is used to modify the outer side, and the template is washed away to obtain the graphene oxide Janus nanosheet of the metal-polyphenol network, wherein the mixed solution is a mixture of ethanol and water.
4. A method for preparing metal-polyphenol network graphene oxide Janus nanosheets as claimed in claim 3, characterized in that: The following steps are involved: S1. Graphene oxide is combined with a solid template through non-covalent interaction. A solid template with a diameter of 1 μm is dispersed in a mixed solution, graphene oxide is added, and stirred at a stirring speed of 500 to 800 rpm to adsorb the graphene oxide on the solid template; the volume ratio of ethanol to water in the mixed solution is 1:1 to 3; S2, modification of the metal-polyphenol network coating, adding polyphenol and metal to the product obtained in step S1, dispersing in a mixed solvent of Tirs-HCl buffer and water, stirring at a stirring speed of 500 to 800 rpm for 10 to 60 min, to obtain microspheres with the metal-polyphenol network coating modified on the outer side of the nanosheet; S3, etching the microspheres obtained in step S2 with an organic solvent to obtain metal-polyphenol network graphene oxide Janus nanosheets; the organic solvent is one of n-hexane, ethyl acetate, dichloromethane and tetrahydrofuran.
5. A method for preparing metal-polyphenol network graphene oxide Janus nanosheets as claimed in claim 4, characterized in that: The following steps are also included: The step S1 also includes the purification of NH2-PS@GO. After the reaction in step S1 is completed, the reaction solution in step S1 is washed and centrifuged with a mixed solution for multiple times to remove unreacted graphene oxide and NH2-PS, and the obtained solid is placed in a vacuum drying oven at 40 to 60° C. and dried for 6 to 8 hours; The S3 also includes the purification of GO JNSs. After the reaction in step S3 is completed, the reaction solution in step 3 is washed and centrifuged with a mixed solution for multiple times to remove the solid template. The precipitate finally centrifuged is washed and filtered with a mixed solution. The obtained solid is placed in a vacuum drying oven at 40 to 60° C. and dried for 6 to 12 hours to obtain the metal-polyphenol network graphene oxide Janus nanosheets.
6. An emulsifier, characterized in that: The emulsifier is the graphene oxide Janus nanosheet of the metal-polyphenol network described in claim 1.
7. A plant essential oil Pickering emulsion, characterized in that: The Pickering emulsion is formed by using the metal-polyphenol network graphene oxide Janus nanosheets in claim 1 or claim 6 as an emulsifier.
8. A plant essential oil Pickering emulsion as claimed in claim 7, characterized in that: The Pickering emulsion is an oil-in-water emulsion; in the Pickering emulsion, the volume ratio of the oil phase to the water phase is 1-10:90-99; in the Pickering emulsion, the concentration of the metal-polyphenol network graphene oxide Janus nanosheets is 0.5-4 mg / mL; The Pickering emulsion is obtained by dispersing the metal-polyphenol network graphene oxide Janus nanosheets of claim 1 into a water phase, adding an auxiliary agent, and then mixing and emulsifying the water phase with an oil phase; The oil phase is one or more of natural plant essential oils such as citronella oil, thymol, carvacrol, turpentine and eugenol; the pH of the water phase is 1 to 12; The auxiliary agent is one or more of chitosan, quaternized chitosan, chitin and gum arabic; The Pickering emulsion has a pH stability value of 3-11.
9. Use of the plant essential oil Pickering emulsion according to any one of claims 7 or 8 for preventing and controlling fungal diseases caused by plant foliar fungi.
Citation Information
Cited By
High-barrier antibacterial polylactic acid packaging material and preparation method thereof
CN120484304A
High-barrier antibacterial polylactic acid packaging material and preparation method thereof
CN120484304B